Keeping order in the brain: The supramarginal gyrus and serial order in short-term memory. (October 2019) - Guidali, Giacomo; Pisoni, Alberto; Bolognini, Nadia; Papagno, Costanza
Abstract: A wide range of human activities are performed sequentially in few seconds. We need to maintain a correct temporal order of words in language, movements in actions, directions in navigation, etc. Therefore, it is plausible, in a more economical perspective, that our brain is equipped with a dedicated mechanism for storing a temporal sequence for a short time. To investigate it, we run four TMS experiments, in which participants performed different short-term memory tasks, i.e., three (verbal, spatial, motor) requiring maintenance of an ordered sequence and one (visual) of a static pattern. We demonstrated, for the first time, that the left supramarginal gyrus is one of the key nodes of the STM network involved in retaining an abstract representation of serial order information, independently from the content information, namely the nature of the item to be remembered, which instead is stored separately.